Investigating the relationship between corporate social responsibility and earnings management: Evidence from Spain - Ester Gras-Gil; Mercedes Palacios Manzano; Joaquín Hernández Fernández (BRQ Business Research Quarterly, 2016)
This article investigates the relationship between corporate social responsibility and earnings management. Using panel data methodology for a sample of Spanish non-financial companies between 2005 and 2012, we find a negative impact of corporate social responsibility practices on earnings management. Corporate social responsibility is related to ethical and moral issues concerning corporate decision-making. Engaging in socially responsible activities not only improves stakeholder satisfaction, but also has a positive effect on corporate reputation. The results show that corporate social responsibility practices may be an organizational device that leads to more effective use of resources, which then has a negative impact on earnings management practices."
Keywords: 650; Corporate social responsibility; Discretionary accruals; Earnings management